2019
DOI: 10.3390/ani9121084
|View full text |Cite
|
Sign up to set email alerts
|

Pleurotus Ostreatus and Volvariella Volvacea Can Enhance the Quality of Purple Field Corn Stover and Modulate Ruminal Fermentation and Feed Utilization in Tropical Beef Cattle

Abstract: This objective is to elucidate the effect of purple field corn stover treated with Pleurotus ostreatus and Volvarialla volvacea on feed utilization, ruminal ecology, and CH4 synthesis in tropical beef cattle. Four male Thai native beef cattle (100 ± 30 kg of body weight (BW) were assigned randomly as a 2 × 2 factorial arrangement in a 4 × 4 Latin square design. Factor A (roughage sources) was rice straw and purple field corn stover and factor B was species of white-rot fungi (P. ostreatus and V. volvacea). Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
4
12
0
1
Order By: Relevance
“…Our ndings indicated that the consumption of PCP did not side effect on DMI and growth performance in goats, suggesting that anthocyanin had no side effects on production performance. Consistent with our research results, Khonkhaeng and Cherdthong [22] who demonstrated that the feeding of anthocyanin-rich purple eld corn stover did not differ DMI, body weight (BW) kg/d and g/kg BW 0.75 in beef cattle. Furthermore, Ban [23] who reported that the addition of phenolic-rich mangosteen peel powder was no effect on DMI of meat goats.…”
Section: Discussionsupporting
confidence: 93%
“…Our ndings indicated that the consumption of PCP did not side effect on DMI and growth performance in goats, suggesting that anthocyanin had no side effects on production performance. Consistent with our research results, Khonkhaeng and Cherdthong [22] who demonstrated that the feeding of anthocyanin-rich purple eld corn stover did not differ DMI, body weight (BW) kg/d and g/kg BW 0.75 in beef cattle. Furthermore, Ban [23] who reported that the addition of phenolic-rich mangosteen peel powder was no effect on DMI of meat goats.…”
Section: Discussionsupporting
confidence: 93%
“…The feeding of the anthocyanin-rich corn silage led to a reduction in aspartate aminotransferase (AST) activity and an increase in superoxide dismutase (SOD) activity in the plasma [21]. In Thailand, the improved population developed by this project is used as roughage and silage for tropical beef cattle [22]. In purple corn, the husk [5,23] and cob [5,23,24] had higher anthocyanin content than the kernel, based on tissue mass [2,25].…”
Section: Introductionmentioning
confidence: 99%
“…presenting a conservative case with respect to bioethanol production. Purple corn stover hybrids with higher structural carbohydrate content have been reported 26,27 . Thus, the effect of low (LSC) and high structural carbohydrate content (HSC) on MESP of the modified processes was evaluated (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…Purple corn stover hybrids with higher structural carbohydrate content have been reported. 26,27 Thus, the effect of low (LSC) and high structural carbohydrate content (HSC) on MESP of the modified processes was evaluated (Table 7). Minimum ethanol selling prices (MESP) decreased with an increase in structural carbohydrate content in purple corn stover (Fig.…”
Section: Effect Of Structural Carbohydrate and Corn Cob Content Variation In Purple Corn Stover On The Process Economics Of The Integratementioning
confidence: 99%
See 1 more Smart Citation